The Effect of Nanoliposomal Curcumin (Cur-NLPs) Proliferation Rate with Cell Counting Kit 8 (CCK-8) and PI3K expression in cervical cancer HeLa cells - Subandi Subandi; Ferry Suciati; Maya Devi Arifiandi; I Wayan Agung Indrawan (Universa Medicina, 2026)
INTRODUCTIONCervical cancer is a major health problem in developing countries. Cisplatin therapy has limitations related to toxicity and drug resistance associated with activation of the PI3K/AKT/mTOR pathway. Curcumin has anticancer activity, but its bioavailability is low; therefore, it has been developed in a nanoliposomal formulation. This study aimed to evaluate the effects of curcumin nanoliposomes (Cur-NLPs) on proliferation and PI3K expression of HeLa cells. METHODSAn experimental study was conducted using HeLa cells, divided into seven groups: negative control, cisplatin 5 µg/mL, and Cur-NLPs groups at 50, 100, 150, 200, and 250 µg/mL. Cell viability was measured using the cell counting kit-8 (CCK-8). Measurements were performed at 24 and 48 hours at a wavelength of 450 nm. Based on viability results, PI3K expression was analyzed at 48 hours using flow cytometry in five groups: negative control, cisplatin, and Cur-NLPs at 100, 150, and 200 µg/mL. Data were analyzed using one-way ANOVA followed by Games-Howell test. RESULTSCur-NLPs significantly reduced HeLa cell viability at 24 and 48 hours (p<0.001). The 200 µg/mL dose showed the most optimal antiproliferative effect, with viability of 38.3% at 24 hours and 18.0% at 48 hours. PI3K expression in the Cur-NLPs group (42.49–45.03%) was lower than that in the cisplatin group (66.78%), but the difference was not statistically significant (p=0.063). CONCLUSIONCur-NLPs inhibited HeLa cell viability in a dose- and time-dependent manner and showed a trend toward reduced PI3K expression. Further replication and analysis of downstream PI3K markers are needed to confirm these findings.